PENINGKATAN PENGETAHUAN KADER MELALUI PENYULUHAN KESEHATAN REPRODUKSI MENGENAI MENOPUSE - Ima Sukmawati; Yuyun Rahayu; Heni Marliany (Universitas Majalengka, 2022)
Abstract Menopause is the permanent cessation of menstruation due to the loss of ovarian activity. Symptoms that appear are sleep disturbances, the emergence of psychological signs in the form of memory loss, emotional changes and depression. The influencing factor is knowledge. The most effective increase in knowledge is through counseling conducted to health cadres, where the level of knowledge of cadres about menopause will help mothers prepare for menopause well. Objective: To increase the knowledge of cadres through health and reproductive education regarding menopause. Methods: (i) Identification of targeted cadres (ii) Socialization, and (iii) Evaluation. Results: obtained from the extension of Cadre Knowledge Improvement through Reproductive Health Counseling Regarding Menopuse, attended by 9 cadres representing Benteng Village, with the result that there was a significant increase of 100% good knowledge. Conclusion: An increase in the knowledge of cadres about menopause will help women who experience menopause to be more prepared to undergo menopause in a healthy manner. Keywords: menopause knowledge, cadre